Profil Peserta Pengembangan Ekonomi Masyarakat Melalui Keterampilan Rajut dan Skills Komunikasi Bagi Guru-Guru Pekanbaru Riau - Radeswandri; Rian Vebrianto; Nurhayati Zein; Musa Thahir (Anotero Lembaga Scientific Pekanbaru, 2020)
Community Service Program was implemented based on problems faced by elementary school teachers in Pekanbaru, including: 1) lack of motivation, knowledge and skills possessed by community and elementary school teachers to improve their creativity and innovation in knitting; 2) lack of community knowledge and creativity to increase economic growth; and 3) lack of guidance from related parties to community and elementary school teachers regarding motivation, creativity, and communication skills. Based on some problems identified, a problem resolved in this activity was: giving assistance in making bags through knitting skills for elementary school teachers in Pekanbaru, Riau. Furthermore, there was also guidance on becoming an MC and other official activities to help participants to be individuals who had confidence and good motivation. The community service activity carried out was Participatory Action Research (PAR) which was conducted using a descriptive approach method. Importantly, population in this study were teachers in Riau Province, especially elementary school teachers in Pekanbaru. Sample of service was chosen by purposive sampling, obtaining elementary school teachers in Pekanbaru. Results of activity could be declared successful in overcoming the problem. It was shown by teachers who strongly agreed with the existence of community service activity as an effort to develop competence, particularly in terms of community economic development through knitting and communication skills for teachers in Pekanbaru.